PENGARUH LAYANAN BIMBINGAN KELOMPOK TEKNIK ROLE PLAYING TERHADAP PERUBAHAN SIKAP BELAJAR DITINJAU DARI ASPEK PANDANGAN SISWA TERHADAP GURU (TEACHER APPROVAL /TA) - Deni Rahman; Arnelis Arnelis; Masril Masril (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2023)
This study discusses how students' learning attitudes develop in a positive direction through role-playing technique group guidance services. The aim of the study was to see whether or not the role playing technique group guidance service was significant to changes in student learning attitudes from the aspect of students' views of teachers (teacher approval/ta). The research method used is the experimental method, namely research that aims to see changes in students' learning attitudes in terms of the aspects of students' views of the teacher (teacher approval/ta ) with group guidance services using role playing techniques. The type of design used in this research is a Quasi-Experimental design with one group pretest-posttest design. The topics discussed in the role-playing technique group guidance service are viewed from the perspective of students' views of teachers. The results of the study indicate that there are significant changes in students' learning attitudes towards a better direction.